Judo, better than dance, develops sensorimotor adaptabilities involved in balance control - Perrin, P.; Deviterne, D.; Hugel, F.; Perrot, C. (Gait and Posture, 2002)
Objectives: Training allows sportsmen to acquire new balance control abilities, possibly differing according to the discipline practised. We compared, by means of static and dynamic posturographic tests, the postural skills of high-level judoists, professional dancers and controls, in order to determine whether these sports improved postural control. Results: With eyes open, judoists and dancers performed better than controls, indicating a positive effect of training on sensorimotor adaptabilities. Yet, with eyes closed, only judoists retained a significantly better stance. Conclusions: These data indicate that the practice of a high-skill activity involving proprioceptive afferences especially improves both performance and balance control.